Polar bear, polar bear, what do you hear? - Martin, Bill, 1916-2004.; Carle, Eric (New York : Holt, 1991)
Zoo animals from polar bear to walrus make their distinctive sounds for each other, while children imitate the sounds for the zookeeper.
Publisher's Weekly.
School Library Journal starred.
Wilson's Children.
1.7.
1.7
K-3
Keywords: Animal sounds -- Fiction; Stories in rhyme; Zoo animals -- Fiction; Animal sounds -- Fiction; Stories in rhyme; Zoo animals -- Fiction